PENGARUH KEPEMILIKAN MANAJERIAL DAN BOOK TAX DIFFERENCES PADA PERSISTENSI LABA - Jumiati, Fitria; Ratnadi, Ni Made Dwi (E-Jurnal Akuntansi, 2014)
Normal 0 false false false EN-US X-NONE X-NONE Reported earnings reports expected quality. Earnings quality is free from income disctionary accruals. Earnings persistence is one component of the quality of their earnings. Managerial ownership and book tax differences are expected to show earnings quality. The annual financial statements for the 200 8 -201 1 term manufacturing companies listed on the Indonesian Stock Exchange selected as the sample. Purposive sampling selected as the sampling technique while multiple regression is used as a data analysis tool. The results showed that managerial ownership has a positive effect on earnings persistence, and while the book tax differences. Large positive book tax differences and large negative book tax differences effect on the persistence of earnings, the large positive book tax differences/large negative book tax differences lower earnings persistence than small book tax differences.
Keywords: earnings persistence, management ownership, book tax differences